Strategi Integrated Marketing Communication (IMC) Café Pupuk Bawang dalam Memperkuat Positioning Merek - Widodo, Herru Prasetya; Rinata, Asfira Rachmat; Fianto, Latif; Ghofur, Mochamad Abdul (Unitri Press, 2025)
Integrated Marketing Communication (IMC) is crucial in the marketing world as it helps create a consistent and unified message for the audience. With IMC, companies can communicate their messages more effectively, through various mutually supporting channels, be it advertising, sales promotions, social media, public relations, and others. This study aims to determine the application of Integrated Marketing Communication (IMC) in strengthening the positioning of Café Pupuk Bawang in Batu City. The method used is a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that IMC is implemented through several aspects such as customer relations, direct promotions, social media, and strengthening brand image. Despite obstacles due to the Covid-19 pandemic, Café Pupuk Bawang was able to maintain its existence through consistent and integrated marketing communications. Pupuk Bawang Café needs to promote itself through various marketing communication activities summarized in Integrated Marketing Communication (IMC), as explained previously, namely the existence of marketing promotion activities in integrated elements, namely Relationships, Structures, Brands, Communication Tools, Messages, Employees, Technology, and Agencies in strengthening positioning. Pupuk Bawang Batu Cafe has performed its duties well, although not as well as possible due to the Covid-19 outbreak. Abstrak Integrated Marketing Communication (IMC) sangat penting dalam dunia pemasaran karena membantu menciptakan pesan yang konsisten dan terpadu untuk audiens. Dengan IMC, perusahaan dapat mengkomunikasikan pesan mereka secara lebih efektif, melalui berbagai saluran yang saling mendukung, baik itu iklan, promosi penjualan, media sosial, public relations, dan lainnya. Penelitian ini bertujuan untuk mengetahui penerapan Integrated Marketing Communication (IMC) dalam memperkuat positioning Café Pupuk Bawang di Kota Batu. Metode yang digunakan adalah pendekatan kualitatif deskriptif dengan teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa IMC dijalankan melalui beberapa aspek seperti hubungan pelanggan, promosi langsung, media sosial, dan penguatan citra merek. Meski terdapat kendala akibat pandemi Covid-19, Café Pupuk Bawang mampu mempertahankan eksistensinya melalui komunikasi pemasaran yang konsisten dan terintegrasi. Pupuk Bawang Café perlu mempromosikan diri melalui berbagai kegiatan komunikasi pemasaran yang terangkum dalam Integrated Marketing Communication (IMC), seperti pada penjelasan sebelumnya yaitu adanya kegiatan promosi pemasaran pada elemen yang terintegrasi yaitu Relationships, Structures, Brands, Communication Tools, Pesan, Karyawan, Teknologi, dan Instansi dalam memperkuat positioning. Kafe Pupuk Bawang Batu telah menjalankan tugasnya dengan baik, meski tidak sebaik mungkin karena wabah Covid-19.